Notes on Some Sanskrit Astrological Authors - Gansten, Martin (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
This paper supplements and corrects the information given in the works of David Pingree regarding four major authors on Tājika or Sanskritized Perso-Arabic astrology from the fourteenth to the seventeenth century: Tejaḥsiṃha, Yādavasūri, Bālakṛṣṇa and Balabhadra. It further contributes information on a fifth such author, Tuka, not discussed by Pingree.